Karakter Anatomi Daun dari Kultur Tunas Artemisia annua L. - , Juliarni; Hamami Alfasani Dewanto; Tri Muji Ermayanti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
Artemisia annua L. produce artemisinin, an endoperoxide sesquiterpene lactone, which is effective against resistant strains of Plasmodium falciparum, the malarial parasite. Artemisinin in foliar tissue are localized entirely in subcuticular space of capitate glandular trichomes. This research was performed to investigate the anatomical structures especially glandular trichomes which associated with artemisinin production in leaves of five different shoot culture clones (A, B, C, D, and E clones). Observation of anatomical characters of leaves was done by making cross-section, while observation of trichomes was performed using Scanning Electron Microscopy. The leaves of five clones showed bifacial anatomical structure. The leaf thickness of E clone was the highest (96.8 µm), while those of four other clones were relatively the same ranging from 62.8 µm to 66.6 µm. Glandular trichomes were distributed throughout the lamina of leaves with the highest distribution in adaxial parts of the leaves. The size of uppermost secretory cells of glandular trichomes was relatively the same in five clones observed. There were variations in density of glandular trichomes in five clones observed. A and B clones had higher density of glandular trichomes i.e. 56.9 and 60.5/mm2, while three other clones had density which range from 43.0 to 49.7/mm2. It was suggested that A and B clones were the potential clones in producing artemisinin in vitro due to their larger leaf size and higher density of glandular trichomes. Keywords : Artemisia annua, shoot culture, anatomical structure of leaf